An Analysis Of Students’ Difficulties In Reading Comprehension At MTs Hidayatul Ulum Karang Anyar - A'yun, Kurrotul; Nizarrahmadi, Nizarrahmadi; Yolanda, Alvina (CV. Jendela Edukasi Indonesia, 2024)
Reading is taught to the eight grades students of junior high school. The aim of the research was to find out what is the most difficult aspect in reading comprehension faced by the eight grade students at MTs Hidayatul Ulum Karang Anyar.The design of this research is a descriptive research design. The population of the research was the ninth grade of MTs Hidayatul Ulum Karang Anyar from 1 classe, with the population were 13 students and the sample was from each class. So, the sample of the research was 13 students. The sample was selected by using simple random sampling technique. To get the data, the researcher gave questionnaire, interview and then analyzed the data by using descriptive statistic calculated by Ms. Excel program. After analyzing the data, the result showed that the most difficult aspect in reading comprehension was the fisth indicator. It is “Students get difficulties in determine main idea” with percentage 78%.